The development of earnings management research - Rath, Subhrendu; Sun, Lan (World Business Institute, 2008)
Earnings management directly affects the overall integrity of financial reporting and significantly influences resource allocation in an economy. The objective of this paper is to help academic researchers, regulators, and investors better understand issues surrounding earnings management. We review the research on earnings management from early 1960s to date. We particularly discuss the changes of different research focus in each stage of the development of earnings management research and the economic consequences of earnings management which directly affects capital resource allocation.